Massive, Open, Online, and National? A Study of How National Governments and Institutions Shape the Development of MOOCs - Tømte, Cathrine; Fevolden, Arne; Aanstad, Siri (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
We explore interpretations of MOOCs around the globe and, in particular, interpretations of MOOCs in Norway. Based on a review of previous studies relevant to these topics, we present two contrasting views on the emergence and development of MOOCs, namely the global interruption view and the national mediation view. We suggest, based on previous studies that MOOCs seem to follow national paths more than global paths. In order to grasp the diversity of understandings of MOOCs, we developed a framework that embraces various aspects of motivation, context, and structure regarding MOOCs. With these two polarised views of MOOC development (the global interruption view and the national mediation view), and the framework serving as an analytical approach, we looked at Norway and analyzed the understandings of the development of MOOCs within this particular national context. The national government seems to have been important in the development of the present MOOCs in Norway, both by organizing a particular group of experts in a dedicated commission to consider the future of MOOC in Norway, and by initiating and giving financial support to the development of MOOCs.